EMOTIONAL ABUSE AND DOMESTIC VIOLENCE : A GLOOMY SNAPSHOT - Wahyu Rahardjo (Jurnal Psikologi, 2007)
Emotional abuse and domestic violence are the widespread social phenomenon in the world. Male domination that supported by the culture pushing the accident to be happened much more and being legitimate in the society. Its affect can give more than just a traumatic syndrome but the continuity of the accident by the children someday. The interesting fact is when we found that the accident can happen also in an opposite thing. Male can be battered by female in heterosexual relationship and the accident can be found in gay and lesbian couple. Even though the cause is different for each other but serious injuries and death become bad common consequences. This cycle must be stopped soon or the accident will always be the big mistake in the family life.Key words : Domestic violence, male dominance, bad common consequences heterosexual relationship and gay/lesbian couple